Membrane currents in visually identified motoneurones of neonatal rat spinal cord. - Takahashi, T (1990)
1. Ionic currents induced by depolarization of motoneurones were analysed by tight-seal, whole-cell recording in thin slices of neonatal rat lumbar spinal cord. Identification of motoneurones viewed under Nomarski optics was confirmed by retrograde labelling with the fluorescent dye, Evans Blue. 2. Under whole-cell voltage clamp, depolarizing command pulses from a holding potential of about -70 mV evoked a fast inward current followed by an outward current. The former was suppressed either by lowering external Na+ concentration or by application of tetrodotoxin (TTX). The apparent dissociation constant of TTX was about 13 nM. 3. The outward current remaining after TTX application was activated by depolarization above -50 mV, showing marked outward rectification in the current-voltage relation. Outward tail currents reversed in polarity near the K+ equilibrium potential calculated from the external and pipette K+ concentrations. 4. When external Ca2+ was replaced by Mg2+, the outward K+ current was suppressed markedly and reversibly. Subtraction of current recorded in Ca2+-free-Mg2+ solution from that in control solution revealed a Ca2(+)-dependent K+ current, IK(Ca) with both a transient, IC, and a sustained component IAHP; its tail current lasted for several hundred milliseconds. 5. The sustained outward current observed in Ca2(+)-free-Mg2+ solution was largely suppressed by external application of tetraethylammonium chloride (30 mM), suggesting that it was mostly the delayed rectifier current, IK. In Ca2(+)-free-Mg2+ solution containing TEA and TTX, another transient outward current was observed, which was inactivated by depolarizing pre-pulses in a time- and voltage-dependent manner. The steady-state inactivation curve indicated 50% inactivation at about -77 mV. 4-Aminopyridine (4-AP, 4 mM) largely and reversibly suppressed this current, whereas it did not affect IK observed in the absence of TEA. It is suggested that the transient outward current corresponds to the A-current (IA). 6. Action potentials were recorded in current-clamp mode. Replacement of external Ca2+ by Mg2+ markedly diminished the after-hyperpolarization. Concomitantly, the repolarizing phase of action potentials was slightly prolonged. In Ca2(+)-free-Mg2+ solution, application of 4-AP markedly prolonged action potential repolarization. In Ca2(+)-free-Mg2+ solution containing 4-AP, addition of TEA-Cl further prolonged the duration of the action potential. It is concluded that three different potassium currents, IC, IA and IK may all contribute to action potential repolarization in rat spinal motoneurones.